Comparison of Microleakage of Cast Posts and Intracanal Pins - Vahid Yegane; Yosef Khlil Sefat; Mahdi Tabrizizadeh; Mohamad Hosein Lotfi Kamrani (Tehran University of Medical Sciences, 2012)
Background and Aims: The seal provided by a root canal filling may be compromised by post space preparation. The aim of this study was to compare coronal microleakage around cast posts and prefabricated pins.Materials and Methods: Thirty-eight extracted single-rooted, maxillary human teeth were prepared with step back method and filled with gutta-percha and sealer. After removing 8 mm of coronal gutta-percha with peeso-reamer drills #2 in twenty canals, the teeth were divided into three groups: cast post & core, prefabricated pin, and gutta-percha (without any post or pin). After thermocycling, the samples were immersed in India ink for seven days. Finally, the specimens were cleared and the coronal microleakage of dye was then measured by the stereomicroscope. The data were analyzed by One-way ANOVA and Tukey HSD tests.Results: According to the results, the mean dye penetration in cast posts, pins, and group without post or pin was 3.3 (0.39), 5.2 (0.47), and 7.2 (0.15) mm, respectively. There was no statistically significant difference between the groups (P>0.05).Conclusion: Considering the importance of adequate filling of crown for prevention of microleakage, the method for coronal filling must be selected with caution. According to the results of this study, no significant difference between microleakage of cast posts and prefabricated pins was observed.